Frequency and type of inheritable mutations induced by γ rays in rice as revealed by whole genome sequencing - Shan Li; Yun-chao Zheng; Hai-rui Cui; Hao-wei Fu; Qing-yao Shu; Jian-zhong Huang (Journal of Zhejiang University-SCIENCE B, 2016)

MiR-28 inhibits cardiomyocyte survival through suppressing PDK1/Akt/mTOR signaling - Rui-Yao Zhu; Di Zhang; Han-Dong Zou; Xiao-Shu Zuo; Qing-Shan Zhou; He Huang (In Vitro Cellular & Developmental Biology - Animal, 2016)

A monotonically declining elevational pattern of bacterial diversity in freshwater lake sediments - Jin Zeng; Dayong Zhao; Huabing Li; Rui Huang; Jianjun Wang; Qinglong L. Wu (Environmental Microbiology, 2016)
Summary The distribution patterns of bacterial communities along elevational gradients remain unexplored in aquatic ecosystems. This study investigated the diversity and community composition of bacteria in the sediments of lakes along a mountainside elevational gradient from 525 to 4 490 m in western China. The bacterial alpha diversity (taxonomic richness and phylogenetic diversity) at different sediment depths decreased monotonically with the increasing elevation, and the beta diversity (dissimilarity between lakes) increased significantly with the increasing elevation distance. Both elevation and chemical variables including pH and carbon/nitrogen ratio were identified as major factors affecting the bacterial diversity. Especially, bacterial alpha/beta diversity was significantly related to both chemical and elevational gradients in the surface sediments, whereas elevation overwhelmed chemical factors in influencing the bacterial alpha/beta diversity in the subsurface sediments. Phylogenetic structure analysis demonstrated that environmental filtering was the most important process affecting the bacterial community assembly along the elevational gradient, and the strength of environmental filtering increased towards high elevations. In summary, we observed for the first time a monotonically decreasing elevational pattern in bacterial diversity of freshwater lake sediments, which is mainly driven by elevation associated environmental factors.

The destruction box is involved in the degradation of the NTE family proteins by the proteasome - Fei-Fei Huang; Ping-An Chang; Lan-Xi Sun; Wen-Zhen Qin; Li-Ping Han; Rui Chen (Molecular Biology Reports, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Transcriptome of High-Sucrose Sugarcane Variety GT35 - Dong-Liang Huang; Yi-Jing Gao; Yi-Yun Gui; Zhong-Liang Chen; Cui-Xian Qin; Miao Wang; Qing Liao; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2016)

Tissue Transglutaminase and Its Product Isopeptide Are Increased in Alzheimer’s Disease and APPswe/PS1dE9 Double Transgenic Mice Brains - Ji Zhang; Suqing Wang; Wei Huang; David A. Bennett; Dennis W. Dickson; Dengshun Wang; Rui Wang (Molecular Neurobiology, 2016)

Celecoxib and octreotide synergistically ameliorate portal hypertension via inhibition of angiogenesis in cirrhotic rats - Jin-Hang Gao; Shi-Lei Wen; Shi Feng; Wen-Juan Yang; Yao-Yao Lu; Huan Tong; Rui Liu; Shi-Hang Tang; Zhi-Yin Huang; Ying-Mei Tang; Jin-Hui Yang; Hui-Qi Xie; et al. (Angiogenesis, 2016)
Abnormal angiogenesis is critical for portal hypertension in cirrhosis. Except for etiological treatment, no efficient medication or regime has been explored to treat the early stage of cirrhosis when angiogenesis is initiated or overwhelming. In this study, we explored an anti-angiogenesis effort through non-cytotoxic drugs octreotide and celecoxib to treat early stage of cirrhotic portal hypertension in an animal model. Peritoneal injection of thioacetamide (TAA) was employed to induce liver cirrhosis in rats. A combination treatment of celecoxib and octreotide was found to relieve liver fibrosis, portal venous pressure, micro-hepatic arterioportal fistulas, intrahepatic and splanchnic angiogenesis. Celecoxib and octreotide exerted their anti-angiogenesis effect via an axis of cyclooxygenase-2/prostaglandin E2/EP-2/somatostatin receptor-2, which consequently down-regulated phosphorylation of extracellular signal-regulated kinase (p-ERK)–hypoxia-inducible factor-1α (HIF-1α)–vascular endothelial growth factor (VEGF) integrated signaling pathways. In conclusions, combination of celecoxib and octreotide synergistically ameliorated liver fibrosis and portal hypertension of the cirrhotic rats induced by TAA via the inhibition of intrahepatic and extrahepatic angiogenesis. The potential mechanisms behind the regimen may due to the inactivation of p-ERK–HIF-1α–VEGF signaling pathway.

Molecular Design, Structural Analysis and Antifungal Activity of Derivatives of Peptide CGA-N46 - Rui-Fang Li; Zhi-Fang Lu; Ya-Nan Sun; Shi-Hua Chen; Yan-Jie Yi; Hui-Ru Zhang; Shuo-Ye Yang; Guang-Hai Yu; Liang Huang; Chao-Nan Li (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Optimization of the Expression Conditions of CGA-N46 in Bacillus subtilis DB1342(p-3N46) by Response Surface Methodology - Rui-Fang Li; Bin Wang; Shuai Liu; Shi-Hua Chen; Guang-Hai Yu; Shuo-Ye Yang; Liang Huang; Yan-Li Yin; Zhi-Fang Lu (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Application of TiO2-organobentonite modified by cetyltrimethylammonium chloride photocatalyst and polyaluminum chloride coagulant for pretreatment of aging landfill leachate - Yi-Jie Zhang; Zhao-Hui Yang; Pei-Pei Song; Hai-Yin Xu; Rui Xu; Jing Huang; Juan Li; Yan Zhou (Environmental Science and Pollution Research, 2016)

Topography‐driven isolation, speciation and a global increase of endemism with elevation - Manuel J. Steinbauer; Richard Field; John‐Arvid Grytnes; Panayiotis Trigas; Claudine Ah‐Peng; Fabio Attorre; H. John B. Birks; Paulo A. V. Borges; Pedro Cardoso; Chang‐Hung Chou; Michele De Sanctis; Miguel M. de Sequeira; et al. (Global Ecology and Biogeography, 2016)
Aim Higher‐elevation areas on islands and continental mountains tend to be separated by longer distances, predicting higher endemism at higher elevations; our study is the first to test the generality of the predicted pattern. We also compare it empirically with contrasting expectations from hypotheses invoking higher speciation with area, temperature and species richness. Location Thirty‐two insular and 18 continental elevational gradients from around the world. Methods We compiled entire floras with elevation‐specific occurrence information, and calculated the proportion of native species that are endemic (‘percent endemism’) in 100‐m bands, for each of the 50 elevational gradients. Using generalized linear models, we tested the relationships between percent endemism and elevation, isolation, temperature, area and species richness. Results Percent endemism consistently increased monotonically with elevation, globally. This was independent of richness–elevation relationships, which had varying shapes but decreased with elevation at high elevations. The endemism–elevation relationships were consistent with isolation‐related predictions, but inconsistent with hypotheses related to area, richness and temperature. Main conclusions Higher per‐species speciation rates caused by increasing isolation with elevation are the most plausible and parsimonious explanation for the globally consistent pattern of higher endemism at higher elevations that we identify. We suggest that topography‐driven isolation increases speciation rates in mountainous areas, across all elevations and increasingly towards the equator. If so, it represents a mechanism that may contribute to generating latitudinal diversity gradients in a way that is consistent with both present‐day and palaeontological evidence.

A new epidioxy-tetracyclic triterpenoid from Poria cocos Wolf - Shiping Li; Zhixin Wang; Rui Gu; Yiwu Zhao; Wenzhe Huang; Zhenzhong Wang; Wei Xiao (Natural Product Research, 2016)

Nitrogen-Fixing and Plant Growth-Promoting Ability of Two Endophytic Bacterial Strains Isolated from Sugarcane Stalks - Yong-Xiu Xing; Chun-Yan Wei; Yao Mo; Li-Tao Yang; Si-Liang Huang; Yang-Rui Li (Sugar Tech, 2016)

Assessing spatial likelihood of flooding hazard using naïve Bayes and GIS: a case study in Bowen Basin, Australia - Rui Liu; Yun Chen; Jianping Wu; Lei Gao; Damian Barrett; Tingbao Xu; Linyi Li; Chang Huang; Jia Yu (Stochastic Environmental Research and Risk Assessment, 2016)

Transcriptome analysis reveals translational regulation in barley microspore-derived embryogenic callus under salt stress - Cheng-hong Liu; Rui-ju Lu; Gui-mei Guo; Ting He; Ying-bo Li; Hong-wei Xu; Run-hong Gao; Zhi-wei Chen; Jian-hua Huang (Plant Cell Reports, 2016)

Multi-Level Assessment of Fracture Calluses in Rats Subjected to Low-Magnitude High-Frequency Vibration with Different Rest Periods - Jiazi Gao; He Gong; Xu Huang; Rui Zhang; Renshi Ma; Dong Zhu (Annals of Biomedical Engineering, 2016)

A new flavane acid from the fruits of Illicium verum - Liang-Deng Wu; Chun-Lan Xiong; Zi-Zhan Chen; Rui-Jie He; Yan-Jun Zhang; Yan Huang; Sheng-Ping Deng; Rui-Yun Yang; Jun Li (Natural Product Research, 2016)

Dietary exposure to lead of adults in Shenzhen city, China - Liubo Pan; Zhou Wang; Zhaoqiong Peng; Guihua Liu; Huimin Zhang; Jinzhou Zhang; Jie Jiang; Nimal Pathiraja; Ying Xiao; Rui Jiao; Wei Huang (Food Additives & Contaminants: Part A, 2016)

Characterization of a NaCl-tolerant β-N-acetylglucosaminidase from Sphingobacterium sp. HWLB1 - Junpei Zhou; Zhifeng Song; Rui Zhang; Limei Ding; Qian Wu; Junjun Li; Xianghua Tang; Bo Xu; Junmei Ding; Nanyu Han; Zunxi Huang (Extremophiles, 2016)

Construction of a bivalent DNA vaccine co-expressing S genes of transmissible gastroenteritis virus and porcine epidemic diarrhea virus delivered by attenuated Salmonella typhimurium - Yudi Zhang; Xiaohui Zhang; Xiaodan Liao; Xiaobo Huang; Sanjie Cao; Xintian Wen; Yiping Wen; Rui Wu; Wumei Liu (Virus Genes, 2016)

Phylogenetic analysis reveals that Japanese encephalitis virus genotype III is still prevalent in swine herds in Sichuan province in China - Rui Wu; Qiao Wang; Hongming Liu; Chunxia Chai; Bo He; Xiaobo Huang; Yiping Wen; Xintian Wen; Qiguai Yan; Xiaoping Ma; Sanjie Cao (Archives of Virology, 2016)

A novel surfactant-, NaCl-, and protease-tolerant β-mannanase from Bacillus sp. HJ14 - Rui Zhang; Zhifeng Song; Qian Wu; Junpei Zhou; Junjun Li; Yuelin Mu; Xianghua Tang; Bo Xu; Junmei Ding; Shucan Deng; Zunxi Huang (Folia Microbiologica, 2016)

Isolation and Expression Analysis of Sucrose Synthase Gene (ScSuSy4) from Sugarcane - Zhong-Liang Chen; Yi-Yun Gui; Cui-Xian Qin; Miao Wang; Qing Liao; Dong-Liang Huang; Yang-Rui Li (Sugar Tech, 2016)

Oral administration of Anabaena-expressed VP28 for both drug and food against white spot syndrome virus in shrimp - Xiao-Hui Jia; Chun-Li Zhang; Ding-Ji Shi; Min-Min Zhuang; Xiang Wang; Rui Jia; Zheng-Yang Zhang; Jie Huang; Yi-Hua Sun; Wen-Yi Qian; Guo-Hong Peng; Pei-Min He (Journal of Applied Phycology, 2016)

Immunogenicity of transmissible gastroenteritis virus (TGEV) M gene delivered by attenuated Salmonella typhimurium in mice - Ying Qing; Jiawen Liu; Xiaobo Huang; Yaqing Li; Yudi Zhang; Jie Chen; Xintian Wen; Sanjie cao; Yiping Wen; Rui Wu; Qigui Yan; Xiaoping Ma (Virus Genes, 2016)

Inhibition of IRF3 expression reduces TGF-β1-induced proliferation of hepatic stellate cells - Ming-ming Ni; Tao Xu; Ya-rui Wang; Ying-hua He; Qun Zhou; Cheng Huang; Xiao-ming Meng; Jun Li (Journal of Physiology and Biochemistry, 2016)

Combination of retinoic acid, dimethyl sulfoxide and 5-azacytidine promotes cardiac differentiation of human fetal liver-derived mesenchymal stem cells - Fuxue Deng; Han Lei; Yunfeng Hu; Linjing He; Hang Fu; Rui Feng; Panpan Feng; Wei Huang; Xi Wang; Jing Chang (Cell and Tissue Banking, 2016)

Erratum to: First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2016)

Seismic Stability of Gravity Retaining Structures by Pseudo-Dynamic Method - Rui Huang; Tang-Dai Xia (Marine Georesources & Geotechnology, 2016)

Notch2 signaling contributes to cell growth, invasion, and migration in salivary adenoid cystic carcinoma - Jing Qu; Min Song; Jian Xie; Xiao-Yu Huang; Xiao-Meng Hu; Rui-Huan Gan; Yong Zhao; Li-Song Lin; Jiang Chen; Xu Lin; Da-Li Zheng; You-Guang Lu (Molecular and Cellular Biochemistry, 2016)